Compression of Economic Space and its Impact on Peripheral Areas - Dvoryadkina, Elena B.; Kaibicheva, Catherine I.; Shurova, Irina I. (International Journal of Economics and Financial Issues, 2016)
The authors use territorial approach for investigating economic space, which makes it possible to explore each of its levels - national, regional and local spaces. Considering a periphery as integral part of an economic space, with a variety of its levels, the authors provide rationalization for a poly-scale approach in the research of a periphery. The article explores the influence of the three forms of the space compression (implosion, polarization of space, and physical space compression) observable in Sverdlovsk oblast on its periphery. The authors single out the patterns of different types of space compression using statistical and mapping methods as well as a historical analysis. There has been identified the following evidence of space compression on peripheral areas: depopulation, decrease in the number of enterprises and organizations, improvement of transport communication. The authors demonstrate the spatial differentiation of regional socioeconomic characteristics in Sverdlovsk oblast, by comparing the contribution of the administrative center and the periphery into the regional economy. There are offered the principal directions of improvement of the regional policy in relation to the peripheral areas. Keywords: economic space, peripheral territories, space compression, region, regional policy. JEL Classifications: O18, R1, R38